Nitrate transformation in soil samples of forest and tea (Camellia sinensis) plantations - BEZBARUAH, BALAMANI; BORA, TARUN; SAIKIA, NEELIMA (The Indian Journal of Agricultural Sciences, 2013)
A comparison was made in 1992 in the rate of nitrate transformation between soil samples from tea [Camellia sinensis (L.) O. Kuntze] plantations from 3 tea-growing regions (Assam 26Â°44’N 94Â° 10’E, Dooars 26Â°54’N 88Â°55’E, Nilgiris 11Â°21’ N 76Â°49" E) and corresponding forest land, by estimating the quantity of nitrate, ammonium and volatilized nitrogen recovered from soil samples amended with potassium nitrate. In all the 3 regions of the forest samples and in several samples of Assam plantation, 85-100% of the nitrate added to the forest samples remained unaltered for 24 hr. The nitrate-reducing activity, although a distinctive characteristic of tea-plantation samples, was related neither to the age of the tea plantation nor to the yield of tea in the respective sections.